Clinical and Epidemiological profile of Anemia in central India - Bhupendra Kumar Ratre; Narmada Prasad Patel; Umesh Patel; Roopesh Jain; V K Sharma (International Journal of Medical Research and Review, 2019)
Background: The present, hospital based prevalence study has been conducted to assess the clinical and epidemiological profile of anemia in central India.Methods: In this study 200 patients of anemia from medical out patients department and indoor wards, age between 15-70 years, randomly selected without any bias for sex, occupation, socio-economic status and duration of disease.Results: This study shows that maximum number of patients (40%) were from age group 21-30 years. Between 15-30 years age group, prevalence of anemia was more in females than males. 57% study population have moderate anemia and 41% patients have severe anemia. Weakness & easy fatigability were most common (100%) presenting symptoms and pallor was most common (98% patients) clinical sign. Microcytic and hypochromic type peripheral smear was most common laboratory findings (59% cases). Nutritional anemia was the most common type of anemia (84%).Conclusions: Nutritional deficiency anemia is the most common cause of anemia among population, and iron deficiency is the most common nutritional deficiency in population.